Flow duration curve a tool to characterize, analyze and management low water in a Semi-Arid context: case of the Tassaout watershed upstream of the Moulay Youssef dam (1978-2016), Central High Atlas, Morocco - CHAKIR, Mohamed; El-GHACHI, Mohamed; GHADBANE, Omar; OUAKHIR, Hassan (Journal of natural sciences, life and applied sciences, 2023)
The watershed of the Tassaout river (upstream of the Moulay Youssef dam) belongs to the semi-arid mountain area, characterized by low rainfall. The scarcity of water resources, the maldistribution of it in time and space as well as the effect of climate change on a global and regional scale, have pushed us to focus on the study of the events of low water levels. The objective of the study of these flows is to know the factors that govern them to improve the management of resources in the watershed. We used in this study the hydrometric data of the Tamsemat station for the chronicle (1978-2016). The methodology adopted is based on the determination and analysis of the thresholds and the intensity of low water flows from the flow duration curve (DC) and the modal flow. The results obtained showed that the characteristic classified flow (Q75), which corresponds to the specific flow of 2.3 L/s/Km2, represents an entry threshold at low water levels for the basin. Thus, and from the intensity thresholds defined by four levels (vigilance, alert, crisis and reinforced crisis), plans and decisions can be taken to guarantee sustainable and integrated management of water resources in the basin studied.